Communicating biological sciences : ethical and metaphorical dimensions - Nerlich, Brigitte, 1956-; Elliott, Richard, 1982-; Larson, Brendon (Ashgate, 2009)
Communicating Biological Sciences discusses the 'ethics' of science communication in light of recent developments in biotechnology and biomedicine. It focuses on the role of metaphors in the creation of visions and the framing of scientific advances, as well as their impact on patterns of public acceptance and rejection, trust and scepticism. Its rigorous investigation will appeal not only to science writers and scientists, but also to scholars of sociology, science and technology studies, media and journalism.